2022
DOI: 10.3389/fpsyg.2022.1012536
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive behavior, boredom, and protective factors among college students during closed-off management of the COVID-19 pandemic in China

Abstract: BackgroundChinese colleges have implemented strict closed-off management in response to the outbreak of a new variant of the new coronavirus, Omicron. But such management measures may lead to more aggressive behavior. The study aimed to determine the associations between boredom and aggressive behavior with aggression and to examine the impact of boredom on aggression through the moderating role of cognitive flexibility.MethodsThe Multidimensional State Boredom Scale, the Reactive–Proactive Aggression Question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 98 publications
1
1
0
Order By: Relevance
“…Moreover, the social role of being a mother may have additionally evoked extra pressure on women to self‐stereotype. It aligns with the existing literature proposing that self‐stereotyping ensures social inclusion and might decrease interpersonal pressures, which mothers might want to avoid (Li et al, 2023). In contrast, low levels of self‐stereotyping might be related to the violation of social roles and hence explain why fewer children are possessed by women with lower levels of self‐stereotyping.…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, the social role of being a mother may have additionally evoked extra pressure on women to self‐stereotype. It aligns with the existing literature proposing that self‐stereotyping ensures social inclusion and might decrease interpersonal pressures, which mothers might want to avoid (Li et al, 2023). In contrast, low levels of self‐stereotyping might be related to the violation of social roles and hence explain why fewer children are possessed by women with lower levels of self‐stereotyping.…”
Section: Discussionsupporting
confidence: 87%
“…In addition to harming themselves, a monotonous environment may lead students to try to alleviate boredom through aggressive behaviour. 27 Hsu and Tsai 28 found that quarantined Twitter users were more aggressive than those non-quarantined, and in the present study, participants even expressed the attempt to commit violent acts against their roommates, which could further jeopardise social stability. Preventive interventions are, therefore, essential to halting self-harm and injury events.…”
Section: Discussionmentioning
confidence: 45%